Efektivitas Pelayanan Publik Masa Pandemi Covid-19 di Desa Persiapan Parianum Kecamatan Muara Bengkal Kabupaten Kutai Timur - Nur Laili Darmayanti; Adam Idris; Iman Surya (Jurnal Ilmu Pemerintahan, 2022)
The results of the study show that in general, public services in the Desa Preparation Parianum have not been fully effective. Where there are several indicators that have not run optimally. As well as the absence of a village information system (SID) which was an inhibiting factor for public services during the Covid-19 pandemic in the Parianum Preparation Village. Because, Parianum Preparation Village is not yet a definitive village. Thereforethe Village Information System (SID) could not be made. There is no clarity on costs and time in each service. Lack of openness of information to the public regarding service procedures provided to the community. Lack of Human Resources (HR) working on e-government. Inadequate facilities and infrastructure to support the running of services. The service system used during the Covid-19 pandemic. The community is satisfied with the services provided even though there is no guarantee of cost and time.